Digitizing Religion: Millenial Generation Da’wah Patterns on Social Media - Agoes Moh. Moefad; Syaifuddin Syaifuddin; Iklima Sholichati (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2021)
The integration of technology has resulted in implementing of the da'wah model growing rapidly and dynamically. The research was conducted by identifying how religion is understood and applied by the millennial generation and how da'wah can be accepted and understood in the millennial era. This study uses descriptive qualitative, and the arrangement uses literature by reviewing, collecting data through a library approach, and collecting information from various digital sources. The research results show that da'wah must be able to position itself in the digital space as an arena of contestation to win the hearts of the people in building a new civilization in the world of da'wah. In addition, many applications and interesting da'wah content have been developed in the era of media digitization. Thus, it impacts efforts to package da'wah messages and disseminate da'wah messages regarding religious language in the digital space. One of them is linking text, narration, images, symbols, and graphics.